The Role and Responsibilities of Public Prosecutors at the Binjai District Attorney's Office in the Criminal Justice Process - Siahaan, Dhea Sintya; Simamora, Janpatar (Golden Ratio of Data in Summary, 2025)
The criminal justice process in Indonesia plays a crucial role in law enforcement, with the Public Prosecutor (JPU) acting as the key actor in prosecuting criminal offenders. This study aims to examine the functions and responsibilities of the JPU at the Binjai District Attorney's Office, as well as the challenges they face in the criminal justice process. Using a normative legal research approach, the analysis focuses on the role of the JPU from the investigation phase to the implementation of verdicts, along with challenges such as limited human resources, budget constraints, societal pressures, and legal complexities. The findings of this study indicate that although the JPU carries significant responsibility in ensuring justice, these challenges may hinder the effectiveness of their duties. This research recommends the development of technology-based training programs, enhanced inter-agency cooperation, and the implementation of management information systems to support the performance of the JPU. It is hoped that these measures will help the JPU at the Binjai District Attorney's Office perform their duties more effectively, thus fostering a fair and transparent judicial system.